Aneurism of splenic artery - Nozar, José; Delgado, Bolívar; Farcic, Antonio; Iraola, María L; Zimmer, Walter; Luvizio, José (Cirugía del Uruguay, 1978)
The paper reports of three cases of aneurism of splenic artery to be added to the scant national case material. The three were diagnosed by different procedures ( operatory exploration; angiography and clinico- operatory diagnosis); two of them were asymptomaitc and in o'ne case there was a serious complication due to rupture of peritoneum. Tactical problems differed due to their association with important diseases. requiring surgical treatment. Of the three, two were treated surgically, in one case by splenectomy and in the other by endoaneurismography; postoperatory evolution was excellent in both.